2017
DOI: 10.3171/2016.8.jns16867
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for recurrence and clinical outcomes in patients with chronic subdural hematoma

Abstract: OBJECTIVE Chronic subdural hematoma (CSDH) is a common type of intracranial hemorrhage in elderly patients. Many studies have suggested various factors that may be associated with the recurrence of CSDH. However, the results are inconsistent. The purpose of this study was to determine the associations among patient factors, recurrence, and clinical outcomes of CSDH after bur hole surgery performed during an 11-year period at twin hospitals. METHODS Kaplan-Meier analysis was performed to evaluate the risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 38 publications
4
49
2
Order By: Relevance
“…The recurrence rate in unilateral CSDH is lower than that of bilateral CSDH, making bilateral hematoma a risk factor for CSDH recurrence [16,19]. This could be due to poor brain re-expansion in bilateral CSDH compared to unilateral CSDH, which may result in a brain parenchymal shift, tearing of the blood vessels, postoperative pneumocephalus and cerebrospinal fluid accumulation in the hematoma cavity, leading to a higher recurrence rate [19,34,35]. Another theory is that patients with bilateral CSDH tend to have a history of brain atrophy, which leads to poor re-expansion, resulting in a higher recurrence rate [19,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recurrence rate in unilateral CSDH is lower than that of bilateral CSDH, making bilateral hematoma a risk factor for CSDH recurrence [16,19]. This could be due to poor brain re-expansion in bilateral CSDH compared to unilateral CSDH, which may result in a brain parenchymal shift, tearing of the blood vessels, postoperative pneumocephalus and cerebrospinal fluid accumulation in the hematoma cavity, leading to a higher recurrence rate [19,34,35]. Another theory is that patients with bilateral CSDH tend to have a history of brain atrophy, which leads to poor re-expansion, resulting in a higher recurrence rate [19,35].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to poor brain re-expansion in bilateral CSDH compared to unilateral CSDH, which may result in a brain parenchymal shift, tearing of the blood vessels, postoperative pneumocephalus and cerebrospinal fluid accumulation in the hematoma cavity, leading to a higher recurrence rate [19,34,35]. Another theory is that patients with bilateral CSDH tend to have a history of brain atrophy, which leads to poor re-expansion, resulting in a higher recurrence rate [19,35]. In our study, bilateral hematoma was found to be a risk factor for postoperative recurrence of CSDH, but was not a risk factor for postoperative AIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In this report, 12 (11.65%) patients showed a recurrence of their hematoma. There were 18 (12%) recurrences among the 149 CSDH cases in the study by Kale et al, 18 nine (10%) recurrences in 90 patients in the study by Han 9 who identified 104 (13.8%) patients with recurrence after surgery for CSDH in a group of 756 patients. However, there is a large amount of variability in the literature concerning this second surgery (see ►Table 6).…”
Section: Discussionmentioning
confidence: 91%
“…Although their findings are inconsistent, numerous studies have reported various potential RF. 4,[7][8][9][10][11][12][13][14][15] Three categories of factors have been recognized: patient comorbidities, imaging data, and surgical modalities. We performed this study to investigate the causal RF for CSDH and to determine whether there is a cumulative effect due to the association of diabetes mellitus (DM) with any other disease that would predict recurrence.…”
Section: Introductionmentioning
confidence: 99%